Alternative Way to Electric Vehicle Battery Technologies as Sustainable Hydrogen Production System without Storage Vessel for Hydrogen Motors and Engine Test - Hasan KÃ¶ten (Universitas Muhammadiyah Magelang, 2025)
Although electric vehicles are becoming more widespread today, the electric batteries used as power sources still have many issues. The main problems include short driving range, long charging times, safety and security concerns, the lack of environmentally friendly electricity production, recycling challenges, high costs, and sustainability issues. In particular, lithium-based electric vehicle batteries are gradually being replaced by alternative battery technologies due to their high cost and limited availability. In this study, we introduce a novel hydrogen production method that can serve as both a fuel for internal combustion engines and an energy source through fuel cells for electric cars. Unlike conventional approaches, this method enables the on-demand production of hydrogen fuel without requiring a hydrogen storage tank, allowing direct use in engines. This study not only eliminates hydrogen storage issues but also presents a new alternative power source to lithium-ion, lithium-air, lithium polymer, magnesium-based and sodium-based electric batteries. As a result, the study describes an environmentally friendly alternative energy source for the automotive industry, a sustainable hydrogen production system, and a solution that enhances safety and security while reducing associated risks.